Aluminum nitride ceramic powder as well as preparation method and application thereof
The preparation of aluminum nitride ceramic powder by using laser ignition-induced combustion synthesis method in the air has solved the problems of complex processes, high energy consumption and difficult to remove impurities, and achieved efficient and safe preparation of aluminum nitride powder.
Patent Information
- Application Number
- CN202411788801.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The existing aluminum nitride powder preparation process is complex, the equipment requirements are high, the energy consumption is high, and the impurities are introduced into the ignition source, making it difficult to remove.
Aluminum nitride ceramic powder is prepared in one step by laser ignition-induced combustion synthesis method in the air, and a high-energy laser beam is used to trigger the combustion synthesis reaction, avoiding the problem of impurities introduced by the ignition source.
The process flow is simplified, energy consumption and equipment requirements are reduced, the purity and production efficiency of aluminum nitride powder are improved, and large-scale production is easy, and production safety is improved.
Smart Images

Figure CN119591409A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic material preparation, and in particular to aluminum nitride ceramic powder and a preparation method and application thereof. Background Art
[0002] Aluminum nitride has the advantages of high thermal conductivity, insulation, low dielectric constant, and small thermal expansion coefficient. It has broad application prospects in the fields of integrated circuit thermal conductive ceramic substrates, electronic device packaging fillers, special structural ceramic materials, etc. At present, the methods for preparing aluminum nitride powder mainly include direct nitridation, carbon thermal reduction, chemical vapor deposition, and self-propagating combustion synthesis. Among them, direct nitridation and carbon thermal reduction are commonly used methods for preparing high-quality aluminum nitride powder in industry. The former is to obtain aluminum nitride powder by reacting aluminum powder with nitrogen or ammonia at 900-1300°C, and the latter is obtained by reacting aluminum oxide, carbon and nitrogen as raw materials at 1500-2000°C. Both of the above reactions need to occur under high temperature conditions, which not only consumes a high amount of energy, but also puts higher requirements on the high temperature and high pressure resistance of the reaction equipment. Chemical vapor deposition is a method for preparing ultrafine, high-purity aluminum nitride. The core is to deposit aluminum nitride powder through gas phase reaction between aluminum volatile substances and ammonia or nitrogen. Although this method can produce high-purity aluminum nitride, its efficiency is low, and the product contains corrosive gases, making it difficult to mass-produce industrial products.
[0003] The self-propagating combustion synthesis method maintains the continuous progress of the reaction through the heat released by its own chemical reaction. Compared with the above-mentioned direct nitridation, carbon thermal reduction nitridation and chemical vapor deposition method, it has the advantages of low energy consumption, high efficiency and easy large-scale production. The conventional combustion synthesis of aluminum nitride is usually carried out in a nitrogen atmosphere of 1 to 10 MPa, and the self-exothermic characteristics of the reaction make the system have an apparent temperature of 1000-1500 ° C. Such high temperature and high pressure reaction conditions make the product aluminum nitride particles coarsened and hard agglomerates serious, which can be suppressed by reducing the nitrogen pressure and adding aluminum nitride diluents. Combustion synthesis of aluminum nitride under near-normal pressure nitrogen has been achieved. The invention application of Sun Siyuan et al., with patent document number CN109020555A, "A method for combustion synthesis of aluminum nitride powder in a slightly positive pressure flowing nitrogen atmosphere", synthesizes aluminum nitride fine powder with a particle size range of 0.5 to 2 μm in a slightly positive pressure flowing nitrogen atmosphere. Zhu Chenguang et al.'s patent document number CN109502561B, "Method for synthesizing aluminum nitride by direct combustion of magnesium-aluminum alloy particles in air", successfully synthesized aluminum nitride powder in air atmosphere, but the product was mixed with a large amount of magnesium oxide and magnesium aluminate impurities due to the introduction of impurities from the ignition source, which was difficult to remove. This invention is derived from this. Summary of the invention
[0004] In order to solve at least one of the above-mentioned technical problems, the purpose of the present invention is to provide a method for synthesizing aluminum nitride ceramic powder by laser ignition induced combustion in air and its preparation method and application, which solves the problems of complex aluminum nitride powder preparation process, high equipment requirements, high energy consumption, and impurities introduced by the ignition source in the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] One of the purposes of the present invention is to provide a method for preparing aluminum nitride ceramic powder, comprising:
[0007] The aluminum powder and aluminum nitride powder in the formula are mixed evenly by ball milling, and the ball milling beads and the mixed powder are separated by a 20-mesh sieve;
[0008] The mixed powder separated by ball milling is placed in a container surrounded by carbon felt, and the container is placed in an air atmosphere;
[0009] The mixed powder in the container is irradiated with a high-energy laser beam to induce the mixed powder to undergo a combustion synthesis reaction, thereby obtaining the aluminum nitride ceramic powder.
[0010] Furthermore, the mass ratio of the aluminum powder to the aluminum nitride powder is 2:8 to 6:4. For example, it can be 2:8 or 3:7 or 4:6 or 5:5 or 6:4. The applicant has found through research that if the proportion of aluminum powder in the raw material is too high, that is, increasing the proportion of aluminum powder will lead to an increase in the content of aluminum oxide impurities in the product, and if the proportion of aluminum powder is too low, the mixed powder will not undergo a combustion synthesis reaction when the above preparation method is used. Therefore, after optimization, the optimal mass ratio of aluminum powder to aluminum nitride powder is 2:8 to 6:4.
[0011] Furthermore, the aluminum powder has a particle size ranging from 0.5μ to 100μm, a purity of 99wt% to 99.9wt%, and a shape of one or more of irregular particles, flakes, and spheres.
[0012] Furthermore, the aluminum nitride powder has a particle size ranging from 1 μm to 100 μm and a purity of 99.2 wt% to 99.9 wt%.
[0013] Furthermore, in the ball milling process, the mass ratio of the ball material (ie, ball milling beads and mixed powder, the ball milling beads in the present invention are preferably zirconia balls with a diameter of 3-10 mm) is 5:1, the rotation speed is 300 rpm, and the ball milling time is 2 to 5 hours.
[0014] Furthermore, the thickness of the mixed powder in the container is 0.5 cm to 3 cm.
[0015] Furthermore, the energy of the high-energy laser beam is 200W to 500W, and the irradiation area is 0.1cm 2~1cm 2 The distance between the light outlet and the mixed powder is 0.1m to 3m. With this design, the high-energy laser beam can be irradiated to any position of the mixed powder to carry out the combustion synthesis reaction.
[0016] Furthermore, the particle size of the aluminum nitride ceramic powder is 0.5μ to 15μm, and the shape is a mixture of irregular particles and spherical particles. The purity of aluminum nitride in the aluminum nitride ceramic powder is higher than 92wt%.
[0017] Another object of the present invention is to provide aluminum nitride ceramic powder obtained by the above-mentioned preparation method, wherein the particle size of the aluminum nitride ceramic powder is 0.5μ~15μm, the shape is a mixture of irregular particles and spherical particles, and the purity of aluminum nitride in the aluminum nitride ceramic powder is higher than 92wt%.
[0018] Another object of the present invention is to provide the application of the aluminum nitride ceramic powder obtained by any of the above-mentioned preparation methods in the fields of ceramic substrates, thermal conductive fillers, structural ceramics, and heat-resistant materials.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The aluminum nitride ceramic powder of the present invention uses aluminum powder and aluminum nitride powder as raw materials, controls the mass ratio of aluminum powder and aluminum nitride powder, and directly performs a combustion synthesis method in air to prepare aluminum nitride powder in one step. The process is simple, the cycle is short, the efficiency is high, and it is easy to mass produce. High-temperature and high-pressure equipment is not required, which reduces production costs and improves production safety. The combustion synthesis reaction is initiated by a laser high-energy beam without an ignition source, which solves the problem of introducing foreign metal impurities caused by using an ignition source to ignite the combustion synthesis reaction in the prior art, and the purity of the obtained aluminum nitride powder is higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A physical picture of a test device for the method for preparing aluminum nitride ceramic powder according to an embodiment of the present invention;
[0023] Figure 2 The XRD phase characterization results of the combustion synthesis product in Example 1 of the present invention;
[0024] Figure 3The SEM microscopic morphology and particle size characterization results of the combustion synthesis product in Example 1 of the present invention;
[0025] Figure 4 The XRD phase characterization results of the combustion synthesis product in Example 2 of the present invention;
[0026] Figure 5 The SEM microscopic morphology and particle size characterization results of the combustion synthesis product in Example 2 of the present invention;
[0027] Figure 6 The XRD phase characterization results of the combustion synthesis product in Example 3 of the present invention;
[0028] Figure 7 The SEM microscopic morphology and particle size characterization results of the combustion synthesis product in Example 3 of the present invention;
[0029] Figure 8 The SEM microscopic morphology and particle size characterization results of the combustion synthesis product in Comparative Example 1 of the present invention;
[0030] Fig. 9 This is the SEM microscopic morphology characterization result of the combustion synthesis product in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0031] In view of the deficiencies in the prior art, the inventors of this case, after long-term research and extensive practical discoveries, proposed an aluminum nitride ceramic powder based on air combustion synthesis and its preparation method and application.
[0032] The following is a further explanation of the technical solution, its implementation process and principle, etc. in conjunction with the preferred embodiments and the accompanying drawings. It should be noted that the following embodiments are only auxiliary explanations of the present invention and should not be used to limit the protection scope of the present invention.
[0033] Example 1
[0034] 20g of aluminum powder with an average particle size of 2.5μm, 80g of aluminum nitride powder with an average particle size of 2μm, and 500g of zirconium oxide ball milling beads were placed in a ball milling jar and placed on a horizontal ball mill mixer for 2h. Afterwards, the ball milling beads were filtered out through a 20-mesh stainless steel sieve. Figure 1 As shown, pour the mixed powder into a container surrounded by carbon felt and expose the container to the air. Adjust the position of the laser collimator so that the laser outlet is 1m away from the mixed powder in the container and the beam is irradiated on the mixed powder. Set the output laser energy to 340W and the laser beam irradiation area to 0.2cm2. When the reaction starts, turn on the laser power supply, emit the laser, and induce the combustion synthesis reaction through the high-energy laser. After the reaction is complete, wait for the material in the container to cool to room temperature to obtain aluminum nitride powder.
[0035] The obtained products were characterized by X-ray diffractometer (XRD) and scanning electron microscope (SEM). Figure 2 The XRD spectrum of the product shows that in addition to aluminum nitride, the product also contains a small amount of aluminum oxide impurities, which is caused by the reaction of aluminum powder with oxygen in the air. Compared with the diffraction peak of aluminum nitride, the diffraction peak of aluminum oxide is very weak. The K value method is used to calculate that the mass proportion of aluminum nitride in the product is 98.2wt%, and the mass proportion of aluminum oxide is 1.8wt%. Figure 3 Under an electron microscope, the product particles show irregular shapes. According to statistics from electron microscope photos, the particle sizes are mainly distributed in the range of 0.5-1μm, and the particle size distribution is narrow.
[0036] Example 2
[0037] 30g of aluminum powder with an average particle size of 2.5μm, 70g of aluminum nitride powder with an average particle size of 2μm, and 500g of zirconium oxide ball milling beads were placed in a ball milling jar and placed on a horizontal ball mill mixer for 2h. Afterwards, the ball milling beads were filtered out through a 20-mesh stainless steel sieve. Figure 1 As shown, pour the mixed powder into a container surrounded by carbon felt and expose the container to the air. Adjust the position of the laser collimator so that the laser outlet is 1m away from the mixed powder and the beam is irradiated on the mixed powder. Set the output laser energy to 340W and the laser beam irradiation area to 0.2cm2. When the reaction starts, turn on the laser power supply, emit the laser, and induce the combustion synthesis reaction through the high-energy laser. After the reaction is complete, wait for the material in the container to cool to room temperature to obtain aluminum nitride powder.
[0038] The obtained products were characterized by X-ray diffractometer (XRD) and scanning electron microscope (SEM). Figure 4 is the XRD spectrum of the product, and the phase composition is the same as that of Example 1. However, the mass proportion of aluminum nitride calculated by the K value method is 96.1wt%, and the mass proportion of aluminum oxide is 3.9wt%. Compared with Example 1, the aluminum oxide content is slightly increased. Figure 5 Under the electron microscope, the morphology of the product particles is still irregular, but compared with Example 1, the particle size tends to increase, and the particle size distribution broadens toward the large size direction.
[0039] Example 3
[0040] 60g of aluminum powder with an average particle size of 2.5μm, 40g of aluminum nitride powder with an average particle size of 2μm, and 500g of zirconium oxide ball milling beads were placed in a ball milling jar and placed on a horizontal ball mill mixer for 2h. Afterwards, the ball milling beads were filtered out through a 20-mesh stainless steel sieve. Figure 1As shown, pour the mixed powder into a container surrounded by carbon felt and expose the container to the air. Adjust the position of the laser collimator so that the laser outlet is 1m away from the mixed powder and the beam is irradiated on the mixed powder. Set the output laser energy to 340W and the laser beam irradiation area to 0.2cm2. When the reaction starts, turn on the laser power supply, emit the laser, and induce the combustion synthesis reaction through the high-energy laser. After the reaction is complete, wait for the material in the container to cool to room temperature to obtain aluminum nitride powder.
[0041] The obtained products were characterized by X-ray diffractometer (XRD) and scanning electron microscope (SEM). Figure 6 The XRD spectrum of the product is the same as that of Example 1 and Example 2, but due to the large proportion of aluminum in the raw material, the amount of aluminum oxide impurities increases. The mass proportion of aluminum nitride calculated by the K value method is 92.9wt%, and the mass proportion of aluminum oxide is 7.1wt%. Figure 7 Under the electron microscope, the product particles tend to stick together. This is because there is too much raw aluminum powder and the aluminum nitride diluent is reduced, resulting in a high reaction temperature. The aluminum powder melts and sticks before nitriding, thus forming a sticky morphology of the product. On the other hand, the particle size calculated from the electron microscope image is significantly larger than that of Example 1 and Example 2, which also indirectly proves the occurrence of melt agglomeration of the raw aluminum powder before nitriding.
[0042] Comparative Example 1
[0043] 30g of aluminum powder with an average particle size of 2.5μm, 70g of aluminum nitride powder with an average particle size of 2μm, and 500g of zirconium oxide ball milling beads were placed in a ball mill jar and placed on a horizontal ball mill mixer for mixing for 2h. Afterwards, the ball milling beads were filtered out through a 20-mesh stainless steel sieve. The mixed powder was poured into a porous stainless steel mold covered with carbon felt, and the mold was placed in a reactor with a high-pressure glass window. The reactor was evacuated to -0.1MPa, and then 2MPa of nitrogen was injected. The laser collimator was adjusted so that the laser was irradiated on the mixed powder through the glass window, and the laser outlet was 1m away from the mixed powder. The output laser energy was set to 340W and the laser beam irradiation area was 0.2cm2. When the reaction started, the laser power was turned on, the laser was emitted, and the combustion synthesis reaction was induced by the high-energy laser. After the reaction was complete, the material in the reactor was cooled to room temperature to obtain a combustion synthesis powder.
[0044] The obtained products were characterized by scanning electron microscopy (SEM). Figure 8is a SEM electron microscope photo of the corresponding product. Compared with Example 2, the morphology of the product of this comparative example has changed, but the particle size distribution of the particles of this comparative example has obviously moved toward the direction of large particles. This is because under a high-pressure nitrogen atmosphere, the probability of collision between aluminum and nitrogen is greatly increased, resulting in a more intense reaction. The rapid reaction process prevents the heat released by the reaction from being dissipated in time, but accumulates locally. On the one hand, the locally accumulated heat causes the aluminum powder in the unreacted adjacent area to melt and agglomerate; on the other hand, the high temperature also causes the aluminum nitride particles in the reaction zone to fuse and grow.
[0045] Comparative Example 2
[0046] Pour 100g of aluminum powder with an average particle size of 2.5μm into a porous stainless steel mold covered with carbon felt, and place the mold in a reactor with a high-pressure glass window. Evacuate the reactor to -0.1MPa, and then inject 0.5MPa nitrogen. Adjust the position of the laser collimator so that the laser shines on the mixed powder through the glass window, and the laser outlet is 1m away from the mixed powder. Set the output laser energy to 340W and the laser beam irradiation area to 0.2cm2. When the reaction starts, turn on the laser power supply, emit the laser, and induce the combustion synthesis reaction through the high-energy laser. After the reaction is complete, wait for the material in the reactor to cool to room temperature to obtain the combustion synthesis powder.
[0047] The obtained products were characterized by scanning electron microscopy (SEM). Fig. 9 The SEM electron microscope photo of the corresponding product. The product particles are obviously agglomerated to form agglomerates of 10 to 20 μm. Different from the above examples, this comparative example does not add aluminum nitride diluent, which makes the raw material powders in direct contact, and high-temperature fusion is difficult to avoid. In addition, the lack of diluent to absorb heat, resulting in an increase in system temperature, also promotes particle growth.
[0048] Comparative Example 3
[0049] The difference from Examples 1 to 3 is that the mass ratio of aluminum powder and aluminum nitride powder is different, and the rest is the same. Specifically, in this comparative example, the aluminum powder is 10g and the aluminum nitride powder is 90g. Figure 1 The test device shown performs a self-propagation synthesis reaction, but no matter how the energy of the laser or the distance between the laser outlet and the raw material powder is adjusted, the mixed powder does not undergo a self-propagation synthesis reaction.
[0050] It should be noted that the test methods involved in the above embodiments can all refer to the existing national standards, industry standards or enterprise standards, and will not be described in detail.
[0051] In the embodiment of the present invention, the aluminum nitride ceramic powder obtained by the preparation method of the above embodiments 1 to 3 is applied to the heat dissipation material, and the applicant finds that it has a good heat dissipation effect, which shows that the aluminum nitride ceramic material obtained by the preparation method of the embodiment of the present invention has broad application prospects in the fields of ceramic substrates, thermal conductive fillers, structural ceramics, heat-resistant materials, etc.
[0052] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0053] The use of headings and sections in this disclosure is not meant to limit the disclosure; each section may apply to any aspect, embodiment, or feature of the disclosure.
[0054] Throughout this disclosure, where a composition is described as having, containing, or comprising particular components, or where a process is described as having, containing, or comprising particular process steps, it is contemplated that the compositions taught by the present invention also consist essentially of or consist of the recited components, and that the processes taught by the present invention also consist essentially of or consist of the recited process steps.
[0055] Unless specifically stated otherwise, use of the terms "include," "includes," "including," "have," "has," or "having" should generally be construed as open ended and non-limiting.
[0056] It should be understood that the order of the various steps or the order in which a particular action is performed is not very important, as long as the teachings of the present invention remain operable. In addition, two or more steps or actions may be performed simultaneously.
[0057] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A method for preparing aluminum nitride ceramic powder, characterized in that: include: The aluminum powder and aluminum nitride powder in the formula are mixed evenly by ball milling, and the ball milling beads and the mixed powder are separated by a 20-mesh sieve; The mixed powder separated by ball milling is placed in a container surrounded by carbon felt, and the container is placed in an air atmosphere; a high-energy laser beam is used to irradiate the mixed powder in the container to induce a combustion synthesis reaction of the mixed powder to obtain the aluminum nitride ceramic powder.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the aluminum powder to the aluminum nitride powder is 2:8 to 6:
4.
3. The preparation method according to claim 1, characterized in that: The aluminum powder has a particle size ranging from 0.5μ to 100μm, a purity of 99wt% to 99.9wt%, and a shape of one or more of irregular particles, flakes, and spheres.
4. The preparation method according to claim 1, characterized in that: The particle size of the aluminum nitride powder ranges from 1 μm to 100 μm, and the purity ranges from 99.2 wt% to 99.9 wt%.
5. The preparation method according to claim 1, characterized in that: In the ball milling process, the ball-to-material mass ratio is 5:1, the rotation speed is 300 revolutions per minute, and the ball milling time is 2 to 5 hours.
6. The preparation method according to claim 1, characterized in that: The thickness of the mixed powder in the container is 0.5 cm to 3 cm.
7. The preparation method according to claim 1, characterized in that: The energy of the high-energy laser beam is 200W to 500W, and the irradiation area is 0.1cm 2 ~1cm 2 The distance between the light outlet and the mixed powder is 0.1m to 3m.
8. The preparation method according to claim 1, characterized in that: The particle size of the aluminum nitride ceramic powder is 0.5μ-15μm, and the shape is a mixture of irregular particles and spherical particles. The purity of aluminum nitride in the aluminum nitride ceramic powder is higher than 92wt%.
9. An aluminum nitride ceramic powder, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the aluminum nitride ceramic powder obtained by the preparation method according to any one of claims 1 to 8 or the aluminum nitride ceramic powder according to claim 9 in the fields of ceramic substrates, thermal conductive fillers, structural ceramics, and heat-resistant materials.
Citation Information
Patent Citations
Method for synthesizing aluminum nitride powder through combustion under micro-positive pressure flowing nitrogen atmosphere
CN109020555A
A method for synthesizing aluminum nitride by direct combustion of magnesium-aluminum alloy particles in air
CN109502561B
Cited By
Preparation method of aluminum nitride powder with low oxygen content
CN121757817A